2015
DOI: 10.1186/s40064-015-1318-7
|View full text |Cite
|
Sign up to set email alerts
|

Highly improved accuracy of the revised PREoperative sarcoma score (rPRESS) in the decision of performing surgery for patients presenting with a uterine mass

Abstract: In 2014, we published an article titled “Novel uterine sarcoma preoperative diagnosis score predicts the need for surgery in patients presenting with a uterine mass” on the preoperative diagnosis of uterine sarcoma, in the SpringerPlus (Nagai et al. in SpringerPlus 2014, 3:678. doi:10.1186/2193-1801-3-678). Subsequently, we received several suggestions from readers, which were used to modify the statistical analysis methods and create a more precise preoperative diagnostic scoring system, which we present here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 6 publications
1
29
0
1
Order By: Relevance
“…However, the appearance of LM may be affected by degeneration, oedema, and/or unusual patterns of growth, making their differentiation from LMS difficult [8; 9]. Conflicting results from prior studies have led to uncertainty regarding the value of qualitative MRI features for differentiating LMS from unusual/atypical LM (ALM) [9-18]. These studies had small numbers of patients with LMS, included few ALM, and grouped various uterine sarcomas (leiomyosarcoma, endometrial stromal sarcoma, carcinosarcoma, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…However, the appearance of LM may be affected by degeneration, oedema, and/or unusual patterns of growth, making their differentiation from LMS difficult [8; 9]. Conflicting results from prior studies have led to uncertainty regarding the value of qualitative MRI features for differentiating LMS from unusual/atypical LM (ALM) [9-18]. These studies had small numbers of patients with LMS, included few ALM, and grouped various uterine sarcomas (leiomyosarcoma, endometrial stromal sarcoma, carcinosarcoma, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Predictive factors in PRESS include age above 49 years old, serum LDH above 279 U/L, positive endometrial cytological findings and MRI findings showing high intratumoural signal intensity on T1 weighted images indicating intratumoural haemorrhage and coagulative necrosis, or a heterogenous mass on T2 weighted images. This scoring system was revised in 2015, and a score of four points or greater suggest a higher risk of uterine sarcoma with a proposed accuracy of 93.7%, positive predictive value of 92.3% and negative predictive value of 94.0% 5. Our patient scored at least six points based on age and LDH levels, signifying a high risk of leiomyosarcoma.…”
Section: Differential Diagnosismentioning
confidence: 88%
“…Some authors have used a diagnostic algorithm based on patient age, LDH levels, endometrial cytological findings, and MRI to determine if morcellation is appropriate; however, others in a meta‐analysis have indicated that morcellation increases the overall and intra‐abdominal recurrence rate as well as death rate in uterine leiomyosarcomas . Bogani also found that very large masses and masses associated with uterine bleeding correlated with US in about 20% and 42%, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Bogani also found that very large masses and masses associated with uterine bleeding correlated with US in about 20% and 42%, respectively . Therefore, comprehensive preoperative workup is desirable including detailed histopathology . If sarcomatosis is suspected, early referral for CRS/HIPEC may improve the prognosis and reduce morbidity .…”
Section: Discussionmentioning
confidence: 99%